2022
DOI: 10.1177/10564926221082494
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Process of Policy Overreaction: The COVID-19 Lockdown Decisions

Abstract: Policy overreaction is a common phenomenon, especially in complex and emergency situations where politicians are led to make decisions fast. In these emergency decisions, emotions run generally high and cognitive processes are often impaired. The conditions of policy overreaction are in place as emotions overwhelm decision makers’ rational processes. Drawing on the response patterns of three countries to the COVID-19 pandemic, we develop a process model of policy overreaction which describes the effects of neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Many countries eventually faced excess mortality rates that were highly unequal across groups, exacerbating preexisting inequalities ( Alsan et al, 2021 ; Schippers et al, 2022 ). Over-reaction was fueled by (unreliable) metrics ( Schippers and Rus, 2021 ; Ioannidis et al, 2022 ) and groupthink, resulting in irrational or dysfunctional decision making ( Joffe, 2021 ; Hafsi and Baba, 2022 ). Furthermore, emotions during crises tend to run high, escalating the risk of harmful overreaction both by policy makers and the general public ( Sunstein and Zeckhauser, 2010 ).…”
Section: Downward Spiralmentioning
confidence: 99%
See 2 more Smart Citations
“…Many countries eventually faced excess mortality rates that were highly unequal across groups, exacerbating preexisting inequalities ( Alsan et al, 2021 ; Schippers et al, 2022 ). Over-reaction was fueled by (unreliable) metrics ( Schippers and Rus, 2021 ; Ioannidis et al, 2022 ) and groupthink, resulting in irrational or dysfunctional decision making ( Joffe, 2021 ; Hafsi and Baba, 2022 ). Furthermore, emotions during crises tend to run high, escalating the risk of harmful overreaction both by policy makers and the general public ( Sunstein and Zeckhauser, 2010 ).…”
Section: Downward Spiralmentioning
confidence: 99%
“…Management research has also shown that long before the crisis within a company becomes apparent, the signs are there, but often go unnoticed or are ignored ( Lorange and Nelson, 1985 ; Fitzgerald, 2005 ). Having to address these problems down the line, often leads to taking drastic steps and overreaction that may further fuel decline ( Lorange and Nelson, 1985 ; Hafsi and Baba, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to the homogenization of policies. Analyzing decision makers' communication during the first wave of COVID‐19 infections, Hafsi and Baba (2023) illustrate how institutional isomorphism led many countries to adopt lockdowns. For example, many North African countries and governments worldwide imitated the French decision to lock down on March 12, 2020.…”
Section: Policy Cues By Geographic Cultural and Institutional Informa...mentioning
confidence: 99%
“…On the other hand, like H2 on the role of cultural similarities, country leaders may be keener to learn from institutional peers, believing institutional compatibility to be essential for policy success (Bennett, 1991; Lejano & Shankar, 2013; Puppim de Oliveira & Berman, 2021). For example, the institutional distance between China and Western countries led to a misinterpretation of events and the perception that the policies adopted in China were primarily a mirage (Hafsi & Baba, 2023). By contrast, South Korea's and Germany's agile and cautionary policy approaches were lauded by many Western countries as a success story (CNN, 2020; Kennedy et al, 2021; Pew Research Center, 2020).…”
Section: Policy Cues By Geographic Cultural and Institutional Informa...mentioning
confidence: 99%